Sosialisasi Literasi Keuangan dan Strategi Pemasaran Digital bagi Siswa SMA Negeri 5 Penajam Paser Utara dalam Mendukung Ekonomi Lokal - Ananda Fadhilah Willyasty Nur Aisyah; Dewi Dewi (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
The development of digital technology demands that the younger generation possess adequate literacy skills. However, observations at SMA Negeri 5 Penajam Paser Utara indicate that students' financial literacy remains low, and their use of social media is not yet productive. Students are not yet accustomed to simple financial record-keeping, are unable to consistently differentiate between needs and wants, and tend to use social media primarily for entertainment. This community service activity aims to improve students' understanding of financial management from an early age and the use of social media as a productive tool through the concept of digital marketing. The method used is educational outreach combined with interactive discussions and simulations of Segmenting, Targeting, and Positioning (STP) strategies in digital marketing. Students are guided to understand the importance of financial literacy and personal financial management. Based on the evaluation results, this activity successfully improved students' understanding of digital marketing and financial management, as well as equipped them with basic knowledge in utilizing digital financial platforms and social media effectively and wisely.